Design and Synthesis of Bioinspired Benzocoumarin‐Chalcones Chimeras as Potential Anti‐Breast Cancer Agents. Issue 33 (2nd September 2021) - Saquib, Mohammad; Baig, Mohammad Hassan; Khan, Mohammad Faheem; Azmi, Sarfuddin; Khatoon, Shahnaaz; Rawat, Arun Kumar; Dong, Jae June; Asad, Mohammad; Arshad, Md.; Hussain, Mohd Kamil
Abstract: The design and synthesis of a library of natural product inspired benzocoumarin‐chalcones chimeras, as potent and selective, novel, anti‐breast cancer scaffold, is reported herein. Twenty‐one new chimeric molecules, 25 –45, were synthesized through an efficient protocol involving the Horner‐Wadsworth‐Emmons‐olefination of β ‐aryl‐ β ‐ketophosphonates with 4‐formyl‐ 2H ‐benzo[ h ]chromen‐2‐ones as the key step, and evaluated for anti‐proliferative activity against a panel of four breast cancer and related cell lines viz. MDA‐MB‐231 (ER‐ve), MCF‐7 (ER+ve), Ishikawa (endometrial cancer) and Hela (cervical cancer). The synthesized molecules showed in vitro anti‐proliferative activity in a range of 7.42 to 74.68 μM (IC50 ). Compounds 33 and 34 showed very good activity, with 34 exhibiting better activity than the standard drugs, tamoxifen and raloxifene. Interestingly, none of the compounds showed cytotoxity against the normal human cell line. To identify the possible targets of the active compounds, molecular docking analysis was conducted to correlate their interaction with the ERα and ERβ receptors. From among the active compounds the docked conformations of 34, at the ERα and ERβ active sites, showed that it fits most favorably in the ligand binding space and shows hydrophobic interactions with the salient residues. Based on the above findings, 34 was identified as a lead molecule for development of more potent anti‐breast cancer agents. Abstract : Twenty‐one novel coumarin‐chalcone chimeric molecules were synthesized via an efficient protocol involving Horner‐Wadsworth‐Emmons‐olefination of β ‐aryl‐ β ‐ketophosphonates as the key step, and evaluated for in vitro anti‐proliferative activity against MDA‐MB‐231, MCF‐7, Ishikawa and Hela cancer cell lines. Compound 34 showed very good activity against MCF‐7 (IC50 =7.42 μM). and MDA‐MB‐231 (IC50 =12.58 μM), better than standard drugs tamoxifen and raloxifene. Moreover, in silico studies established that 34 favorably fits in the ligand binding space and forms hydrophobic interactions with the salient residues.